2017
DOI: 10.1186/s12955-017-0596-x
|View full text |Cite
|
Sign up to set email alerts
|

An equivalence study: Are patient-completed and telephone interview equivalent modes of administration for the EuroQol survey?

Abstract: BackgroundTo determine if the EuroQol Health Related Quality of Life survey produces equivalent results when administered by phone interview or patient-completed forms.MethodsPeople awaiting hip or knee arthroplasty at a major metropolitan hospital participated. They were randomly assigned to receive the EuroQol Health Related Quality of Life survey via telephone, followed by a patient completed form 1 week later, or vice versa. Equivalence was determined using two one-sided tests (TOST) based on minimal clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 17 publications
1
32
1
1
Order By: Relevance
“…Some countries applied a sampling design, whereas other countries did not, which might lead to a more accurate reflection of representativeness for the former. Although mode of administration might contribute to observed differences, a recent study showed equivalence between various modes of administration using the EQ-5D [32]. Further variability between countries might be caused by translations of the different versions of the EQ-5D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some countries applied a sampling design, whereas other countries did not, which might lead to a more accurate reflection of representativeness for the former. Although mode of administration might contribute to observed differences, a recent study showed equivalence between various modes of administration using the EQ-5D [32]. Further variability between countries might be caused by translations of the different versions of the EQ-5D.…”
Section: Discussionmentioning
confidence: 99%
“…Standardization for age was performed to avoid bias due to the fact that some populations have a relatively higher proportion of elderly people. Age standardization of reported problems by dimension and EQ VAS were based on the European population structure using Eurostat data from 2010 [26], using the following proportions for each age group: 11% (18-24), 17% (25)(26)(27)(28)(29)(30)(31)(32)(33)(34), 18% (35-44), 18% (45-54), 15% (55-64), 11% (65-74), and 10% (75 +).…”
Section: Cross-country Analysismentioning
confidence: 99%
“…Primary patient-reported outcomes included the Oxford Knee Score (OKS; at 90 and 365 days) 16 and the EuroQol Visual Analogue Scale for "today" health (EQ-VAS; at 35, 90 and 365 days). 17 The OKS comprises 12 joint-specific Likert-style questions about pain and functional impairment during the previous month; responses are scored from 0 (maximal discomfort/ pain or maximal impairment) to 4 (no pain/discomfort or impairment), providing a total score out of 48; higher scores indicate better joint status. EQ-VAS is a scaled measure of how the respondent perceives their own overall health on the day, from 0 (worst health imaginable) to 100 (best health imaginable).…”
Section: Discussionmentioning
confidence: 99%
“…Baseline scores were based on responses by patients to the printed survey, while follow-up scores were collected by telephone interview; the two approaches have been shown to be equivalent. 17 Rehabilitation charges were determined from the perspective of the provider. Adjustments for inflation were made if the source document for costs was published before 2015.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation